Methods in Mouse Atherosclerosis - Andrés, Vicente; Dorado, Beatriz; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This volume reviews available mouse models of atherosclerosis, basic aspects of disease initiation and progression, and the visualization of atherosclerotic lesions with invasive and non-invasive techniques that are widely used both in basic research and in the clinic. The chapters catalogue a wide range of in vitro and in vivo experimental methods used for atherosclerosis research, including thorough protocols and valuable notes based on the authors’ personal wet lab experience. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Methods in Mouse Atherosclerosis will be a valuable working guide for researchers performing mouse-based atherosclerosis studies.
Use of Mouse Models in Atherosclerosis Research -- Cytokines and Immune Responses in Murine Atherosclerosis -- Intravital Microscopy for Atherosclerosis Research -- Non-invasive Molecular Imaging of Mouse Atherosclerosis -- Oil Red O and Hematoxylin and Eosin Staining for Quantification of Atherosclerosis Burden in Mouse Aorta and Aortic Root -- Isolation, Culture, and Polarization of Murine Bone Marrow-Derived and Peritoneal Macrophages -- Isolation of Mouse Primary Aortic Endothelial Cells by Selection with Specific Antibodies -- Isolation and Culture of Aortic Smooth Muscle Cells and In Vitro Calcification Assay -- Immunostaining of Macrophages, Endothelial Cells, and Smooth Muscle Cells in the Atherosclerotic Mouse Aorta -- Immunostaining of Lymphocytes In Mouse Atherosclerotic Plaque -- Flow Cytometric Analysis of Immune Cells Within Murine Aorta -- In Vitro Differentiation of Naïve CD4+ T cells: A Tool for Understanding the Development of Atherosclerosis -- Quantification of Apoptosis in Mouse Atherosclerotic Lesions -- Quantification of Cellular Proliferation in Mouse Atherosclerotic Lesions -- Quantification of in vitro Macrophage Cholesterol Efflux and in vivo Macrophage-Specific Reverse Cholesterol Transport -- In vitro Macrophage Phagocytosis Assay -- Glucose and Insulin Tolerance Tests in the Mouse -- Wire Myography to Study Vascular Tone and Vascular Structure of Isolated Mouse Arteries -- Generation of Aorta Transcript Atlases of Wild-type and Apolipoprotein E-null Mice by Laser Capture Microdissection-based mRNA Expression Microarrays -- Analysis of Gene and Protein Expression In Atherosclerotic Mouse Aorta By Western Blot and Quantitative Real-Time PCR -- Bone Marrow Transplantation in Mice to Study the Role of Hematopoietic Cells in Atherosclerosis -- Tandem Stenosis to Induce Atherosclerotic Plaque Instability in the Mouse -- Detection of Intraplaque Hemorrhage in Mouse Atherosclerotic Lesions -- Mechanical Stabilization of Mouse Carotid Artery for in vivo intravital Microscopy Imaging of Atherogenesis -- Intravital Microscopy in the Cremaster Muscle Microcirculation for Endothelial Dysfunction Studies. - Fluorescent Molecular Tomography for in vivo Imaging of Mouse Atherosclerosis -- In vivo 18F-FDG-PET Imaging in Mouse Atherosclerosis -- Magnetic Resonance Imaging of the Atherosclerotic Mouse Aorta.
Keywords: Molecular biology; Cardiology; Animal models in research; Molecular Medicine; Cardiology; Animal Models